Addressing the Issue of Disadvantaged Youth Seeking Work - Emma Hollywood; Valerie Egdell; Ronald McQuaid (Social Work & Society, 2012)
In the UK a significant number of young people do not make successful transitions into further education, training or employment on leaving school, which has been exacerbated further by the current economic crisis.  Drawing on in-depth qualitative interview data, this paper examines two Third sector programmes in the UK that can be seen moving away from 'work-first' employment activation and focusing instead on promoting the individual capabilities of disadvantaged, unemployed youth in finding work.  When this move is considered through a capability approach perspective, questions are raised about the voice of young people, as their aspirations can be limited because of the social contexts in which they live.  It is argued that enabling unemployed youth to choose the work that they have reason to value cannot be achieved without taking into account the importance of the external context; and so while young people's choices may be developed through providing role models etc. it is still a choice shaped and restrained by the context of wider labour markets and education and training opportunities; and the personal and social barriers that inhibit young people from entering work.